IgA expressed by glomerular mesangial cells is involved in the pathogenesis of IgA nephropathy - Zhang, Haidong; Deng, Zhenling; Gao, Yueming; Li, Qi; Zhang, Lu; Wang, Yue (Frontiers in Immunology, 2025)
BackgroundThe widely accepted “multi-hit hypothesis” of IgAN pathogenesis was challenged, as efficient depletion of CD20+ B cells failed to reduce serum galactose-deficient IgA1 (Gd-IgA1) or proteinuria in IgAN patients. Our group has discovered glomerular mesangial cells (GMCs) as another source of IgA, while immunoglobulin produced by non-B cells (non-B Ig) participating in several inflammatory and neoplastic diseases arose as a new concept in immunology. It is still unclear whether IgA produced by GMCs participates in the pathogenesis of IgAN and what its preliminary mechanism is.MethodsThe transcription of IGHA1 and its associated function in GMCs were demonstrated by single-cell RNA sequencing (scRNA-seq) analysis. IGHA1 transcription in glomerular mesangium was detected in para-cancerous renal tissues by fluorescence in situ hybridization (FISH). Staphylococcus aureus enterotoxin B (SEB), Toll-like receptor 4 (TLR4) antagonist, and small interfering RNA (siRNA) were used to investigate the pro-inflammatory effect of Gd-IgA1 and its overproduction pathway. The IgAN model was established in μMT mice (lacking B lymphocytes with reduced serum IgA) and mice with IGHA conditional knockout in GMCs to observe the causality between GMC-expressed IgA and the formation of IgAN.ResultsExpression of IgA in GMCs was reconfirmed by detecting IGHA1 transcription in single cells and in para-cancerous renal tissue in situ. Gene set enrichment analysis (GSEA) indicated that IGHA1 transcription in GMC was significantly associated with response to bacterium, innate immune response, complement activation, and galactose metabolism. Cultured human GMC experiments revealed that SEB could stimulate Gd-IgA1 overproduction through the TLR4 signaling pathway, and Gd-IgA1 deficiency in GMCs relieved the extracellular matrix component (ECM) deposition and C3 and IL-6 production induced by SEB. Mesangial IgA deposition and ECM expansion pattern in the μMT mouse IgAN model were similar to those in Balb/c mice, and mice with IGHA conditional knockout in GMCs relieved glomerular inflammatory response and alleviated the hematuria and proteinuria in the mouse IgAN model.ConclusionWe reconfirmed the expression of IgA in GMCs and demonstrated that overexpression of Gd-IgA1 in GMCs induced by SEB through the TLR4 pathway in human GMC may play an important role in inducing an inflammatory response in IgAN.